ANALYSIS OF MODELS FOR PREDICTING INSOLVENCY (BANKRUPTCY) OF BUSINESS ENTITIES (European Journal of Interdisciplinary Research and Development, 2026)
This article presents the concept of insolvency (bankruptcy) and its content, analysis methodology. The article describes the foreign models of bankruptcy prediction and the indicators used in them. As a result of research, was formed the author's approach to preventing insolvency (bankruptcy).